ð˜‰ð˜¢ð˜¤ð˜ªð˜ð˜ð˜¶ð˜´ ð—Œð—‰. RZ2MS9 AND THE BACTERIA-FREE FILTRATE IN THE SEED GERMINATION AND GROWTH OF MAIZE SEEDLINGS - Andrade, Pedro Avelino Maia de; Pimenta, Lucas Smith; Cardillo, Bruno Ewerton da Silveira; Marcon, Joelma; da Silva, JosÃ© AntÃ´nio; de Azevedo, JoÃ£o Lucio; Novembre, Ana Dionisia da Luz Coelho; Quecine, Maria Carolina (REVISTA DE AGRICULTURA, 2020)
Seed vigor and seedling growth directly impact the early stages of maize production. These traits might be improved with the use of bioinoculants. This work aimed to evaluate the influence of Bacillus sp. RZ2MS9 and its bacteria-free filtrate in the seeds’ germination rate (G) and speed (GSI) and seedlings’ length (SL) and dry mass (SDM) of two maize hybrids. After receiving experimental treatments, seeds of maize hybrids DKB390 and 30A37PW® were grown at a germinator at 25oC and 90% humidity. GSI was evaluated daily while G (%), SL (cm) and SDM (mg.10 seeds-1) were evaluated after 7 days. GSI and SDM were higher in both hybrids treated with Bacillus sp. RZ2MS9. The bacteria-free filtrate produced higher GSI in the 30A37PW® hybrid only in comparison to the control treatments. Thus, the Bacillus sp. RZ2MS9 and its extracellular secreted compounds might comprise alternative tools to improve development and production of maize plants.